2021
DOI: 10.3389/fimmu.2021.753092
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate Metabolism Facilitates IL-1β Production in Inflammatory Macrophages

Abstract: Increasing evidence support that cellular amino acid metabolism shapes the fate of immune cells; however, whether aspartate metabolism dictates macrophage function is still enigmatic. Here, we found that the metabolites in aspartate metabolism are depleted in lipopolysaccharide (LPS) plus interferon gamma (IFN-γ)-stimulated macrophages. Aspartate promotes interleukin-1β (IL-1β) secretion in M1 macrophages. Mechanistically, aspartate boosts the activation of hypoxia-inducible factor-1α (HIF-1α) and inflammasome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…While high content of aspartic acid can be a toxin, which induces hyperexcitability of neurons, eliciting degeneration of neurons with excess, which will ultimately develop to cognitive impairment ( 22 ). Another, current research has suggested the accelerative role of aspartate metabolism in the inflammatory responses ( 23 ). Related studies generally have pointed out that the pathogenesis of cognitive impairment in SCZ is closely related to the abnormal immune system ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…While high content of aspartic acid can be a toxin, which induces hyperexcitability of neurons, eliciting degeneration of neurons with excess, which will ultimately develop to cognitive impairment ( 22 ). Another, current research has suggested the accelerative role of aspartate metabolism in the inflammatory responses ( 23 ). Related studies generally have pointed out that the pathogenesis of cognitive impairment in SCZ is closely related to the abnormal immune system ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the finding that glutamine supplies both carbon and reduced nitrogen for the formation of aspartate suggests a potentially important role of aspartate in M1-like macrophages. Indeed, aspartate has been shown to promote IL-1β secretion in M1 macrophages by boosting the activation of HIF-1α ( 59 ). In regard to other amino acids, we detected only weak labeling of U 15 N glutamine into valine and isoleucine ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Asparagine is a metabolite from aspartate metabolism. Large amounts of evidence indicate that aspartate could promote a macrophage-mediated inflammatory response and attenuate intestinal damage caused by endotoxins in weaned pigs [ 77 , 78 ]. No differences were observed in serum and ileal mucosa metabolites in pigs fed with different doses of botanical blend 2, which is consistent with intestinal microbiota data and indicates no dose response was observed in botanical blend 2 regarding intestinal microbiota and metabolomics.…”
Section: Discussionmentioning
confidence: 99%